Recurrent vulval fibroepithelial polyp with pregnancy: a rare presentation - Armo, Meena; Agrawal, Sarita; Minj, Manoj; Babbar, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
A fibroepithelial polyp (FEP) is a relatively uncommon benign condition of vulva, mainly of reactive origin, occurs in women of reproductive age, mostly during pregnancy. Here is a case which presented with bilateral vulval mass, for that she underwent surgical excision. Histopathological examination revealed bilateral fibroepithelial vulval polyp. After 4 years of uneventful interval same female came with term pregnancy with a huge vulval mass on left side, having similar characteristic features as previous one. Emergency cesarean section followed by excision of polyp in the same sitting done. Histopathological report confirmed the finding of fibroepithelial polyp this time also. Only few cases of recurrent fibroepithelial polyp of vulva associated with pregnancy have been reported till date.